ANALISA DEBIT LIMPASAN PADA PERENCANAAN SISTEM DRAINASE BERWAWASAN LINGKUNGAN DI KECAMATAN PASIRJAMBU DAN KECAMATAN CIWIDEY, KABUPATEN BANDUNG: indonesia - Amaliah, Khairunnajah; Astono, Widyo; Siami, Lailatus (Jurnal Sains & Teknologi Lingkungan, 2025)
Ecodrainage planning in Pasirjambu District, Ciwidey District. In 2017 the district experienced a fairly high rain intensity and there was a change in the function of the forest area in the upstream area, so that the Ciwidey Sub-watershed experienced an overflow. To overcome this problem, an environmentally friendly drainage is planned by adding complementary structures, namely a reservoir pool as a flow barrier. The available surface runoff discharge is 11.68 m3/s at outlet S.8. The discharge will be reduced by 8 m3/s into the reservoir with a storage volume of 2,208 m3. Meanwhile, another reservoir originating from the Ciwidey River with a discharge of 21.007 m3/s requires a storage volume of 210.07 m3. The water stored in the embung will be used for irrigation purposes, so that this reservoir can reduce areas prone to flooding and prone to inundation but can also increase rice production as a livelihood for the community.